Education, Economic Growth, and Population on Bandung and Surabaya Unemployment - Wulandari, Tiara Putri; Yuliani, Zahra (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This research aims to analyze the influence of education level, economic growth, and population on the unemployment rate in Bandung and Surabaya during the period 2015-2024. Utilizing a quantitative approach with panel data, this research employs the Random Effects Model, selected based on the results of the Chow test, Hausman test, and Lagrange Multiplier test. The findings indicate that the three independent variables collectively have a significant effect on the unemployment rate. However, when analyzed partially, none of the variables show a statistically significant individual effect on unemployment. This insignificance suggests that unemployment issues are not solely determined by education, economic growth, or population size, but are also influenced by other factors such as the mismatch between skills and labor market needs, the quality of education, and the regional economic structure that has yet to become fully inclusive. Therefore, the results of this study highlight the need for a more integrated and locally responsive employment development strategy. This research contributes to policymakers by providing insights for designing concrete and sustainable measures to reduce unemployment